Análisis financiero de los activos corriente y su incidencia en la rentabilidad de la empresa Dismero S.A. - Dicao Valencia, José Javier (2019)
In the following work the importance of making a financial analysis in the company and the influence incurred in each department will be announced, for this the basic concepts will be applied to later consider the methods mentioned in the study carried out and through these identify the opportunities and threats that the company has to make decisions, in order to maximize the resources of the entity; This will be done according to the financial indicators that these measure and control the efficiency and effectiveness of the work carried out so that it will be able to implement strategies to the market, rethink the objectives of the entity and with the help of these it will be able to build customer loyalty and granting them Shareholders better profitability to your company